THE EFFECT OF SERVICE QUALITY ON SATISFACTION AND BEHAVIORAL INTENTION IN THE OUTPATIENT UNIT AT PRIMAYA HOSPITAL SEMARANG - Novi Tri Lesmono (Jurnal Scientia, 2023)
This thesis is entitled "The Effect Of Service Quality On Satisfaction And Behavioral Intention In The Outpatient Unit At Primaya Hospital Semarang." The study aims to analyze the impact of service quality on customer satisfaction and behavioral intention at the outpatient unit of Primaya Hospital Semarang. The research involved 150 respondents, with the majority aged between 25-34 years, employed in the private sector, and holding a Bachelor's degree (S1). The data was analyzed using the Partial Least Square (PLS) method. The research results indicate that the respondents are generally satisfied with the quality of service and have a positive intention to recommend and pay more. From the PLS analysis, a significant relationship was found between service quality, satisfaction, and behavioral intention. This study provides valuable insights into the factors influencing patient satisfaction and behavioral intentions at the outpatient unit of Primaya Hospital Semarang, which could be valuable information for the hospital management in enhancing their service quality.